2021
DOI: 10.1177/17474930211012545
|View full text |Cite
|
Sign up to set email alerts
|

Off-hour effect on time metrics and clinical outcomes in endovascular treatment for large vessel occlusion: A systematic review and meta-analysis

Abstract: Background There is an ongoing debate on the off-hour effect on endovascular treatment (EVT) for acute large vessel occlusion (LVO). Aims This meta-analysis aimed to compare time metrics and clinical outcomes of acute LVO patients who presented/were treated during off-hour with those during working hours. Summary of review Structured searches on the PubMed, Embase, Web of Science, and Cochrane Library databases were conducted through February 23rd, 2021. The primary outcomes were onset to door, door to im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“… 17 A recent meta-analysis also indicates that off-hour is associated with prevalent delays before EVT. 19 But some studies indicate that pre-EVT time metrics are not influenced by the off-hour effect. 14 15 Disparities in time metrics might result from the differences in EVT workflows in various stroke centres and heterogeneous definitions of off-hour.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 17 A recent meta-analysis also indicates that off-hour is associated with prevalent delays before EVT. 19 But some studies indicate that pre-EVT time metrics are not influenced by the off-hour effect. 14 15 Disparities in time metrics might result from the differences in EVT workflows in various stroke centres and heterogeneous definitions of off-hour.…”
Section: Discussionmentioning
confidence: 99%
“… 1 13–18 The definition of off-hour varies in different studies. 19 Some studies define the off-hour group according to arrival time, 2 13–15 17 20–23 and some according to groin-puncture time. 1 3 16 18 24–26 Whether the effect will change or not when grouped by different reference time point remains uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…Many healthcare systems have since established or improved 24/7/365 coverage of EVT, while others are still struggling with this endeavor 2–4. However, even when complete coverage has been achieved, the quality of EVT may differ across regions or in different time windows 5 6…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have investigated the influence of treatment time of day on patient outcome in stroke with large vessel occlusion, but most of these studies were either small,9 focused on single specialized tertiary care centers10 11 and/or investigated cohorts before publication of large randomized controlled trials on EVT 12. Such variations likely explain the different results of these individual studies, although a meta-analysis found treatment delays and lower rates of successful recanalization in stroke patients treated with EVT outside core working hours 6. A recent study from the German Stroke Registry found worse outcomes in patients treated with EVT who had longer time intervals to recanalization, reporting longer door-to-groin time at night-time and weekends 13…”
Section: Introductionmentioning
confidence: 99%
“…5 Time of day and day of week have been demonstrated to influence performance metrics and clinical outcomes on different medical conditions. [6][7][8] Arrival during nonregular working hours or nighttime has been associated with time delays in workflow times in patients with an acute ischemic stroke, [9][10][11] although contradictory results have been reported about its influence on clinical outcome. 12,13 Nighttime might increase time delays during acute stroke workflow stages and influence differently the 2 transport modalities, given that the management of patients initially evaluated at a local stroke center requires greater coordination and may be more susceptible to delays during interhospital transfers and understaffed healthcare services.…”
mentioning
confidence: 99%